Japanese Military Sexual Slavery. The transnational redress movement for the victims - Yim, Sejung Sage; Chung, Thomas; Min, Pyong Gap (2020)
This volume examines the redress movement for the victims of Japanese military sexual slavery in South Korea, Japan, and the U.S. comprehensively. The Japanese military forcefully mobilized about 80,000-200,000 Asian women to Japanese military brothels and forced them into sexual slavery during the Asian-Pacific War (1932-1945). The Japanese government has not made a sincere apology and compensation to the victims until today